URGENCY OF WIRETAPPING IN GETTING EVIDENCE IN CRIMINAL MEASURES - Afifah, Wiwik (DiH: Jurnal Ilmu Hukum, 2020)
AbstractExtraordinary crime requires a special step in its disclosure. Wiretapping is one of the efforts to gather evidence to uncover the crime. But in the RKUHP, wiretapping will also be applied to general criminal offenses. This places the law enforcers have access to personal interests in the name of the law. So vulnerable to human rights violations. Therefore it is important to conduct a study of the urgency of wiretapping in criminal acts. The research method used is normative juridical and the method used is the statutory and conceptual approach. The results of this study indicate that there is an urgency to conduct wiretapping arrangements on specific criminal acts and not on general crime This urgency arises based on the characteristics of the crime. The author's suggestion is that wiretapping of general criminal acts in the criminal procedure code should be abolished, and the state drafted a law on tapping that specifically regulates material and formal law.Keywords: criminal acts; urgency of wiretappingAbstrakKejahatan luar biasa membutuhkan langkah khusus dalam pengungkapannya. Penyadapan adalah salah satu upaya untuk mengumpulkan bukti untuk mengungkap kejahatan. Namun dalam RKUHP, penyadapan juga akan diterapkan pada pelanggaran pidana umum. Ini menempatkan penegak hukum memiliki akses ke kepentingan pribadi atas nama hukum. Sangat rentan terhadap pelanggaran HAM. Oleh karena itu penting untuk melakukan studi tentang urgensi penyadapan dalam tindak pidana. Metode penelitian yang digunakan adalah yuridis normatif dan metode yang digunakan adalah pendekatan hukum dan konseptual. Hasil penelitian ini menunjukkan bahwa ada urgensi untuk melakukan pengaturan penyadapan pada tindakan kriminal tertentu dan bukan pada kejahatan umum. Urgensi ini timbul berdasarkan pada karakteristik kejahatan. Saran penulis adalah bahwa penyadapan tindakan kriminal umum dalam kode prosedur pidana harus dihapuskan, dan negara membuat undang-undang tentang penyadapan yang secara spesifik mengatur materi dan hukum formal.Kata kunci: tindak pidana; urgensi penyadapan